Spectrally efficient multicarrier modulation system for visible light communication - T. Deepa; Harshita Mathur; K. A. Sunitha (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Visible Light Communication (VLC) has become an accolade to its radio frequency counterpart. In VLC system, orthogonal frequency division multiplexing (OFDM) has drawn much attention, because of simple equalization, high spectral efficiency, high data rate and robustness to intersymbol interference (ISI). Besides, there are emerging applications that ought to be gotten with low latency and high reliability. To diminish power requirements with no transmission capacity extension, Trellis coded modulation (TCM) is utilized as a part of the framework in which the free distance of trellis diagram is equivalent to the minimum distance between the points of constellation focuses in partitioned subsets, which augments the coding gain up i.e. the performance parameter viably. TCM together with VLC-OFDM enhances the transmission execution in reasonable frameworks. In this paper, we propose OFDM which is based on TCM and is planned and exeuted for digitized OFDM frameworks by presenting delta sigma modulation (DSM) considering VLC channel. Simulation results show that the proposed TCM based VLC-OFDM offers incredible robustness against noises and nonlinear degradation.